Pembuatan Lengan Senapan Angin 300x100x30 mm, Kaliber 4 mm, Komposit Sabut Kelapa, Kapasitas 0,67 Pasang/Jam - Lazuardi Lazuardi; Syamsul Hadi; Nundiah Zuhrohfi Immaroh; Muhammad Akhlis Rizza; Sugeng Hadi Susilo; Maryono Maryono (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2026)
The weight of the 4 mm caliber air rifle arm (hand grip) with an initial weight of 450 g and the abundance of underutilized coconut fiber are the problems faced. The purpose of the manufacture is to obtain an air rifle arm measuring 300x100x30 mm, 4 mm caliber from coconut fiber composite material with an air rifle arm weight of around 250 g. The manufacturing method includes: air rifle arm design; selection of coconut fiber material with a diameter of 0.3-0.6 mm with drying at a temperature of 80°C for 2 hours; making a left and right pair of air rifle arm molds; molding coconut fiber composites with polyester resin and 0.5% hardener with a random fiber arrangement with a length of 10 mm and a volume fraction of 20%; natural hardening (curing) for 24 hours; making a standard specimen of coconut fiber composite with the composition for impact tests with three replications; analysis of impact test results data; quality and dimension inspection of the air rifle arm composite. The result of the manufacturing process is an air rifle arm weighing 238 g, with a specific impact strength of 0.087 J/mm², with a total production cost of IDR 157,000/pair, and a production duration of 90 minutes/pair, which results in the total weight of the rifle decreasing from 6.5 kg to 6.3 kg.